2009
DOI: 10.1177/0165025409104525
|View full text |Cite
|
Sign up to set email alerts
|

False belief understanding: Children catch it from classmates of different ages

Abstract: Two experiments were conducted to compare the false belief understanding of children who have no siblings, but have classmates of different ages in kindergarten. In Experiment 1, 4- and 5-year-olds completed two unexpected location tasks. We found that 4-year-olds with classmates of different ages performed significantly better than those with classmates of the same age. This result was replicated in a larger sample in Experiment 2 in which the children were asked to complete an unexpected location task and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Specifically, past studies have shown that children's language ability (Astington & Baird, 2005; Harris et al, 2005; Hughes et al, 2005; Lillard & Kavanaugh, 2014), especially in the context of perspective-taking that is needed for everyday conversation (Deleau, 2012), and children's involvement in pretend play, particularly pretend role play in which children enact another person's perspective (Astington & Jenkins, 1995; Harris, 2000, 2005; Lillard & Kavanaugh, 2014; Taylor, Carlson, Maring, Gerow, & Charley, 2004; Youngblade & Dunn, 1995) are associated with ToM abilities. In addition, a large body of research has shown that the extent to which caregivers attend to and discuss mental states has an impact on ToM development (Meins et al, 2002; Ruffman, Perner, & Parkin, 1999) as does social interaction with children of different ages (Cassidy, Fineberg, Brown, & Perkins, 2005; Cutting & Dunn, 1999; Ruffman, Perner, Naito, Parkin, & Clements, 1998; Wang & Su, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, past studies have shown that children's language ability (Astington & Baird, 2005; Harris et al, 2005; Hughes et al, 2005; Lillard & Kavanaugh, 2014), especially in the context of perspective-taking that is needed for everyday conversation (Deleau, 2012), and children's involvement in pretend play, particularly pretend role play in which children enact another person's perspective (Astington & Jenkins, 1995; Harris, 2000, 2005; Lillard & Kavanaugh, 2014; Taylor, Carlson, Maring, Gerow, & Charley, 2004; Youngblade & Dunn, 1995) are associated with ToM abilities. In addition, a large body of research has shown that the extent to which caregivers attend to and discuss mental states has an impact on ToM development (Meins et al, 2002; Ruffman, Perner, & Parkin, 1999) as does social interaction with children of different ages (Cassidy, Fineberg, Brown, & Perkins, 2005; Cutting & Dunn, 1999; Ruffman, Perner, Naito, Parkin, & Clements, 1998; Wang & Su, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It seemed that centre-based care could play a protective role for children with lower-educated mothers: on one hand, professionals provide stimulating contexts and aware educational practice (for a wider discussion, see: Molina, 2016; Molina et al, 2016); on the other hand, in day care services children experience stable and numerous relationship with peers that could foster ToM development: debate is still open about a positive effect of the presence of siblings in the family and peers in kindergarten, observed in some studies (McAlister and Peterson, 2007; Wang and Su, 2009) but not in others (Das and Babu, 2004; Molina and Bulgarelli, 2012a). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ToM tasks typically used dolls, cartoons, computer‐generated shapes, or stories rather than real minds (Wang & Su, ). However, a few studies have been about real‐life real‐time minds (Birch & Bernstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, this slightly later age estimate means the child has had some period of schooling ahead of ToM becoming relatively mature. Indeed, notwithstanding the earlier development of meta‐representational abilities (Perner, ), it may well be that what happens socially at school or even schooling itself is what drives the subsequent maturation of children's ToM (Turnbull, Carpendale & Racine, ; Wang & Su, ).…”
Section: Introductionmentioning
confidence: 99%